Myocardial ischemia and left ventricular diastolic dysfunction in HIV infected patients and asymptomatic for coronary artery disease (Research, Society and Development, 2021)
Highly active antiretroviral therapy (HAART) allows chronicity of AIDS evolution, leading to association of other pathologies such as coronary artery disease (CAD). Myocardial ischemia (MI) and left ventricular diastolic dysfunction (LVDD) evaluation in HIV-infected patients may favor primary prevention of CAD. The study aimed to evaluate frequencies of MI and LVDD in the population living with the human immunodeficiency virus (PLHIV) and asymptomatic for CAD. We analyzed data from 110 HIV-infected patients who underwent clinical and laboratory evaluation, treadmill exercise stress test, and transthoracic echocardiogram, and compared it with 2,619 healthy individuals from the control group (non-HIV and non-CAD), selected from the database. HIV-infected patients presented lower average age (51.5 ± 7.7), systemic arterial hypertension (28.0%) and dyslipidemia frequencies (32.0%). On the other hand, their MI frequency was twice as high (14.7%); and diastolic dysfunction (DD) percentage was higher in ischemic patients (45.5%). In the HIV-infected group, MI frequency was 10.0%, while that of DD was 18.2%. MI was twice as frequent among HIV infected patients compared to uninfected, despite lower frequency of risk factors for CAD. Non-ischemic patients living with HIV had a frequency of DD more than twice compared to the control individuals.